(NsOWREMENNAQ PRIKLADNAQ ALGEBRA (B/s - (NbIRKGOFF(B, (NgARRETs; (NbARTI(B, (NtOMASs; (NmANIN(B, (N`(B.(Ni(B.s ((NmOSKWA (B:s (NmIR(B,s, 1976)
(NsPISOK LIT(B. (NI PREDM(B. (NUKAZ(B. (NS(B. 390 - 396s
Garrett Birkhoff, Thomas C. Bartee
Keywords: (NaLGEBRA PRIKLADNAQs